A new polyploid species of mecardonia (gratioleae, plantaginaceae) from South America - Greppi, Julián Alejandro (2017)
Fil: Greppi, Julián Alejandro. Instituto Nacional de Tecnología Agropecuaria. Instituto de Floricultura; Argentina.